Knee arthroplasty can preserve cognitive function in patients with severe knee osteoarthritis - Juneyoung Heo; Ji-Hoon Baek; Chang Hyun Nam; Taehyeon Kim; Hye Sun Ahn; Su Chan Lee (PLoS ONE, 2025)
Background This study examined how the clinical and radiological severity of knee osteoarthritis (OA) and various treatment methods affect cognitive function. Method This prospective study included patients with knee pain or discomfort who visited a single institution between July 2017 and November 2022. Patients with Kellgren–Lawrence (K–L) grade 0 or treatable dementia were excluded from this study, and 88 patients were followed up for an average duration of 2.4 ± 1.3 years. Overall, 55 patients had K–L grade 4, of whom 45 who did not improve after >3 months of conservative treatment underwent knee arthroplasty. Results Among patients with K–L grade 4, the decrease in the Mini-Mental State Examination score in patients who underwent surgery was significantly lower than that in other patients who received conservative treatment only. Conclusion Knee arthroplasty can reduce the decline in cognitive function in patients with severe knee OA of K-L grade 4 who do not respond to conservative treatment. Even if pain is controlled with conservative treatment, the decline in cognitive function in patients with OA is faster than the age-related decline observed in the general population.